2018
DOI: 10.1002/gps.4963
|View full text |Cite
|
Sign up to set email alerts
|

Examining differences in neuropsychiatric symptom factor trajectories in empirically derived mild cognitive impairment subtypes

Abstract: Objective The aim of this study was to examine neuropsychiatric symptom (NPS) factor severity progression over time in empirically derived (ED) mild cognitive impairment (MCI) subtypes. Methods Participants in the Alzheimer's Disease Neuroimaging Initiative study diagnosed with MCI by Alzheimer's Disease Neuroimaging Initiative protocol using conventional clinical (CC) criteria (n = 788) were reclassified using cluster analysis as amnestic, dysnomic, dysexecutive MCI, or cluster‐derived normal (CC‐Normal) usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Scientific literature has considered that different patterns of NPS are associated with distinct MCI subtypes, and differences in conversion rates between NPS could be partially consequence of these clinical subtypes. For example, more severe agitation/hyperactivity symptoms over time are observed in MCI patients with anamnestic profile subtype 30 . Other explanations have been formulated connecting the occurrence of particular NPS with specific brain networks or circuits in the brain 32 or proposing that brain changes, presented in preclinical stages, could be explaining the differential clinical progression of patients, including NPS manifestations 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Scientific literature has considered that different patterns of NPS are associated with distinct MCI subtypes, and differences in conversion rates between NPS could be partially consequence of these clinical subtypes. For example, more severe agitation/hyperactivity symptoms over time are observed in MCI patients with anamnestic profile subtype 30 . Other explanations have been formulated connecting the occurrence of particular NPS with specific brain networks or circuits in the brain 32 or proposing that brain changes, presented in preclinical stages, could be explaining the differential clinical progression of patients, including NPS manifestations 33 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to statistical heterogeneity, many studies used variants in NPI-Q scoring procedures, with the most common being a dichotomized presence/absence (de Vito et al, 2018; Sayegh & Knight, 2014; Siafarikas et al, 2018; Thakur et al, 2021) and 4-point ordinal severity (Feghali et al, 2021; Seidl & Massman, 2016; Siafarikas et al, 2021; Trzepacz et al, 2013). Many studies also eliminated items because they had low rates of endorsement in their samples, high cross-loadings, and/or failed to load adequately on a single factor (de Vito et al, 2018; Sayegh & Knight, 2014; Seidl & Massman, 2016; Thakur et al, 2021; Trzepacz et al, 2013). These modifications to the test item structure further obscure cross-study comparison.…”
Section: Differences In Statistical Methodologymentioning
confidence: 99%
“…There may also be true differences in the structure of the NPI-Q depending on the population sampled. Specifically, many studies limited their inclusion to select participants (e.g., those diagnosed with probable Alzheimer’s disease [AD]) or cognitive impairment severity or only included those who had BPS concerns (de Vito et al, 2018; Feghali et al, 2021; Sayegh & Knight, 2014; Seidl & Massman, 2016; Trzepacz et al, 2013). For instance, two studies using NPI-Q and NPI found variations in item loadings and number of factors when EFA was performed separately in AD severity subgroups (Aalten et al, 2003; Siafarikas et al, 2018).…”
Section: Differences In Statistical Methodologymentioning
confidence: 99%
See 2 more Smart Citations